An audit of the physiotherapy management of paraplegic patients with sacral pressure sores - D. Pather; W. Mudzi (AOSIS, 2013)
Introduction: Pressure sores are the most common complication post spinal cord injury that requires patients to be on bed rest. Patient bed rest delay rehabilitation and may lead to other complications associated with immobility. This study sought to establish the treatment interventions physiotherapists provide to patients with sacral pressure sores and the factors that they consider when deciding whether the patient should receive physiotherapy in the ward or gym. Methods: This was a questionnaire based survey of physiotherapists working in spinal cord injury rehabilitation units in South Africa. The self-designed questionnaire was sent to all the main spinal rehabilitation units in the country (14) located in Gauteng, Kwa-Zulu Natal, Western Cape, Eastern Cape and Free State provinces. Results: Thirty-nine physiotherapists from a total of 51 completed the questionnaires (76% response rate). The most common treatment practice for patients with sacral pressure sores was bed rest (98%). The most common physio-therapy practices (70%) included were upper limb muscle strengthening, upper and lower limb passive movements, positioning into prone and side lying and passive stretching. The choice of treatment environment was influenced by doctors' orders and the size, grade and duration of the pressure sores. Conclusion: Direct involvement in pressure sore management in South Africa seem to be less than in other parts of the world. If we are to minimise the pressure sore impact, it appears like we need more focus on gait re-education and standardised ADL programmes and patient treatment in the gym to possibly maximise healing and rehabilitation.